Enacting a Consumer Protection Law in Ghana: Possible lessons from the UK Consumer Rights Act 2015 (Law Research Review Quarterly, 2020)
For many years, the trend of legislation has been piecemeal with a fusion of the rules of laws for the protection of consumer and non-consumer buyers. However, the complexity of accessing the fragmented laws and their unsuitability in dealing with contemporary consumers issues have led to the adoption of a Consumer Protection Policy 2014 with the primary object of providing a consumer tailored regime for the protection of consumers in Ghana. While the adopted 2014 Policy document is currently before the Attorney General Department to be drafted into a Bill for Parliament consideration, the present article appraises the comprehensiveness of the existing law and the adopted Consumer Protection Policy 2014 in effectively responding to the problems of consumers in Ghana. This is explored in comparison with the approach of the UK Consumer Rights Act 2015 while bearing in mind the peculiar circumstances in Ghana. This article argues that whereas the effort of the government is so far commendable, there are noticeable unresolved consumer concerns. Of particular concern is consolidating the laws on consumer contracts and coverage of the law on the supply of services to consumers. This paper, therefore, submits that addressing these concerns is vital to ensuring that consumers are provided with a comprehensive and effective regime in Ghana.